The Effect of Build Orientation on Liquid Absorption and Wear of 3D-Printed Denture Materials - Ikhlas, Muhammad; Cahyono, Sukmaji Indro; Prayoga, Benediktus Tulung; Dharmastiti, Rini; Arifvianto, Budi; Mahardika, Muslim (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Up till now, denture has been widely used for resolving dental problems, especially those due to attrition. The attrition of tooth enamel could lead to wear and lowering the functions of normal teeth. So far, denture is made conventionally by using heat curing method in a mold. However, the complex geometries of teeth and oral cavity has led to the use of the more advanced techniques, such as additive manufacturing. In this research, the denture material fabricated by using digital light processing (DLP) additive manufacturing was studied in term of their liquid absorption capability and wear behavior. The specimen was printed with three build orientations, namely 0°/180°, 90°/90°, and 45°/135°. These are the degree between printing direction against sliding direction. An immersion and wear test were carried out in artificial saliva liquid. The result showed the lowest weight gain and dimensional change in the specimens printed with 90°/90° and 45°/135°. Meanwhile, the specimens prepared with build orientation of 0°/180° or printed with layer parallel to sliding direction demonstrated the smallest value of wear factor, indicating a better wear resistance compared to the others. A visual examination of the worn surface indicated delamination, abrasion and cracking as the possible wear mechanisms of the printed denture materials.